A Kaleidoscope of Immigrants’ Dilemma in Benyamin’s Novel Jasmine Days - Ravita (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The JCB inaugural award-winning novel Jasmine Days, was initially written in the Malayalee language under the title Mullappoo Niramulla Pakalukaby Benyamin and it has been translated into English by Shehnaz Habib in 2018.It depicts a precise portrayal of the social, historical and religious background of the immigrant communities in a Middle Eastern country in Arab land.The representation of a female perspective by a male author makes the book more distinctive.It also offers an unvarnished anatomy of the contemporary immigrant society that has been devastated by a revolution, divided by nationality and loyalty, exposing the oppressive politics of citizenship and the strategic reduction of a community to a non-entity.In addition, it highlights the societal attitudes towards religion, morality and patriarchal family structures, besides questioning the government agencies.The novel projectsa new point of view of Immigrants’ dilemma by presenting a diasporic Pakistani family in an unnamed City in a Middle Eastern country.